Prediction of remission of type 2 diabetes mellitus after bariatric surgery - O. V. Kornyushin; I. S. Sakeian; E. N. Kravchuk; D. I. Vasilevsky; I. N. Danilov; A. E. Neimark (Сахарный диабет)
Type 2 diabetes prevalence is increasing dramatically worldwide. Conservative therapy doesn’t bring stable effect and is often insufficient, not to mention the lack of prospects to cure the disease. Fortunately, accumulating evidence points towards the notion that a complete remission of type 2 diabetes is feasible following a choice of surgical interventions. The efficacy of bariatric surgery in particular for achieving glycemic control has highlighted surgery as a candidate curative intervention for type 2 diabetes. When compared to intensive medical therapy and lifestyle intervention, metabolic surgery has shown superiority in achieving reducing number of medications and metabolic factors improvement, which translates in long-term benefits on diabetes progression and complications. Understanding factors that predict diabetes remission can help to select patients who will benefit most from bariatric surgery and to choose the most effective type of operation. This literature review analyzes studies of the most significant clinical and biochemical predictors of remission of type 2 diabetes mellitus after bariatric interventions, as well as highlights well-known mathematical prediction models.